2000
DOI: 10.1016/s0277-9536(00)00086-1
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes as barriers in breast screening: a prospective study among Singapore women

Abstract: Health care systems do not exist in isolation, but rather, as part of the larger social and cultural mosaic. In particular, perceived attitudes are major obstacles in health promotion exercises. This problem is especially true for non-white populations where little is known about the prevailing social and cultural perceptions towards western biomedical prescriptions. To further our understanding of Asian women's acceptance of mammograms, three attitudinal indexes are conceptualised, constructed and validated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 19 publications
11
74
0
1
Order By: Relevance
“…Specifically, women with no formal education and a negative history of breast cancer were less likely to have undergone mammography during the previous last two years than graduate women with a positive history of breast cancer. Several studies have also revealed that education level is an important socio-demographic variable linked with mammography use (Straughan and Seow, 2000;Juon et al, 2002;Finney et al, 2003) which proves the study result. Besides, mammography utilization was high among women with a family history of breast cancer (Murabito et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Specifically, women with no formal education and a negative history of breast cancer were less likely to have undergone mammography during the previous last two years than graduate women with a positive history of breast cancer. Several studies have also revealed that education level is an important socio-demographic variable linked with mammography use (Straughan and Seow, 2000;Juon et al, 2002;Finney et al, 2003) which proves the study result. Besides, mammography utilization was high among women with a family history of breast cancer (Murabito et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Based on the results from the regression analysis, modalities in this sample of women include barriers and and Wu, 2005), Asian American (Wu and Ronis, 2009) and Singaporean women (Straughan and Seow, 2000). In addition, in our study, women who had family members and/or friends diagnosed with breast cancer were more not been consistently reported in previous literature as Americans (Lee-Lin et al, 2007).…”
Section: Discussionmentioning
confidence: 53%
“…63 Similarly, several other studies have suggested that if their family or social group members hold divergent views about their illnesses and treatments, patients might get confused whether or not to adhere to medication leading to higher chances of poor medication adherence. [68][69][70][71] However, other studies have shown that patients who received support from their family members while taking medications had better adherence to medication regimens. 58,72 So, adherence to medication is not only influenced by the patient's views towards the disease and drugs but also by other people's concern and attitude towards the disease sufficient to influence the patient's belief.…”
Section: 6466mentioning
confidence: 99%